2017
DOI: 10.1111/jace.14776
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcination atmosphere on monodispersed spherical particles for highly optical transparent yttria ceramics

Abstract: Highly sinterable powders are required for the fabrication of transparent ceramics. Here, we studied the effects of calcination atmosphere on the characteristics of monodispersed spherical Y2O3 powders, such as crystallite size and particle density, for high optical transparent ceramics. It was found that vacuum calcination around the crystallization temperature is the crucial step to eliminate intragranular pores in the spherical particle. The fast decomposition rate in a vacuum creates smaller crystallites, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 55 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…Jung et al studied the effects of calcination atmosphere on Y2O3 particles. 43 They found that vacuum calcination is a crucial step to realize a dense spherical Y2O3 particle. After calcined at 1100 °C under vacuum, the pores inside the synthesized particles were notably reduced and the sinterability of Y2O3 was obviously promoted.…”
Section: Fabrication Of Sesquioxide Ceramics 271 Powder Preparationmentioning
confidence: 99%
“…Jung et al studied the effects of calcination atmosphere on Y2O3 particles. 43 They found that vacuum calcination is a crucial step to realize a dense spherical Y2O3 particle. After calcined at 1100 °C under vacuum, the pores inside the synthesized particles were notably reduced and the sinterability of Y2O3 was obviously promoted.…”
Section: Fabrication Of Sesquioxide Ceramics 271 Powder Preparationmentioning
confidence: 99%
“…the melting temperature for Y2O3 is ~ 2430 ℃. 124 Using conventional crystal growth technology to fabricate sesquioxide single crystals is very challenging. 125 In view of their importance for high power lasers, different research groups in the world have intensively investigated on the fabrication technology for sesquioxide-based laser ceramics with high quality.…”
Section: Introductionmentioning
confidence: 99%